Computational Molecular Phenotypic Analysis of PTPN22 (W620R), IL6R (D358A), and TYK2 (P1104A) Gene Mutations of Rheumatoid Arthritis - Shaik, Noor Ahmad; Banaganapalli, Babajan (Frontiers in Genetics, 2019)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder of bone joints caused by the complex interplay between several factors like body physiology, environment and genetic back ground. The recent meta-analysis of GWAS has expanded the total number of RA-associated loci to more than 100, out of which approximately ~97% (98 variants) loci are located in non-coding regions, and the other ~3% (3 variants) are in three different non-HLA genes i.e. TYK2 (Trp620Arg), IL6R (Asp358Ala) and PTPN22 (Prp1104Ala). However, whether these variants prompt changes in protein phenotype with regards to its stability, structure, and interaction with other molecules, remains unknown. Thus, we aim to scrutinize how these mutations cause changes in protein phenotype using diverse types of computational prediction methods. Both wildtype and mutant protein structures of PTPN22 (W620R), IL6R (D358A) and TYK2 (P1104A) were modeled and studied for structural deviations. Furthermore, we have also studied the secondary structure characteristics, solvent accessibility and stability, molecular interaction deformities caused by the amino acid substitutions. We observed that simple nucleotide predictions of SIFT, PolyPhen, CADD, FATHMM yields mixed findings in screening the RA-missense variants which showed a ≥ P-value threshold of 5 x 10-8 in genome wide association studies. However, structure-based analysis confirms that mutant structures shows subtle but significant changes at their core regions, but their functional domains seems to lose wild type like functional interaction. Our findings suggest that the multidirectional computational analysis of clinically potential RA-mutations could act as a primary screening step before undertaking functional biology assays.